The versions of the origin of the word «philosophy» - Rayhert, Kostyantyn (Actual Problems of Mind, 2017)
The paper considers four versions of the origin of the word «philosophy». The first version: the word «philosophy» comes from Pythagoras. The second version: the word «philosophy» was already used in the second half of the 5-th century BC in Athens. Author proposes two versions of his own. The first one: to consider politician Pericles as a possible author of the word «philosophy». The second one: to consider historian Herodotus as a possible author of the word «philosophy».